2013
DOI: 10.1016/b978-0-12-407708-9.00002-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Cytokine Gene Expression

Abstract: Epigenetics encompasses transient and heritable modifications to DNA and nucleosomes in the native chromatin context. For example, enzymatic addition of chemical moieties to the N-terminal “tails” of histones, particularly acetylation and methylation of lysine residues in the histone tails of H3 and H4, plays a key role in regulation of gene transcription. The modified histones, which are physically associated with gene regulatory regions that typically occur within conserved noncoding sequences, play a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 492 publications
(814 reference statements)
0
27
0
Order By: Relevance
“…KDM6B is one of the two histone demethylases (the other being KDM6A or UTX) that removes the methyl mark from H3K27, relieving the suppression of transcription and inducing an inflammatory response (Falvo, Jasenosky, Kruidenier, & Goldfeld, 2013). Murine studies have confirmed demethylated H3K27 is heavily enriched at IL17a/IL17f locus in Th17 cells and also controls RORγt expression (Mukasa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…KDM6B is one of the two histone demethylases (the other being KDM6A or UTX) that removes the methyl mark from H3K27, relieving the suppression of transcription and inducing an inflammatory response (Falvo, Jasenosky, Kruidenier, & Goldfeld, 2013). Murine studies have confirmed demethylated H3K27 is heavily enriched at IL17a/IL17f locus in Th17 cells and also controls RORγt expression (Mukasa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This process is transcriptionally regulated and involves the induction of lineage-specific transcription factors (Li et al, 2014). Furthermore, complex chromatin remodeling responses that control the accessibility of transcription factors to their target genes provide another regulatory mechanism in Th cell differentiation (Falvo et al, 2013). As compared to other aspects of Th cell induction, signals and pathways that trigger either “permissive” or “repressive” chromatin remodeling responses during Th cell generation remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, even the complexity of a given sample may be unknown; even in blood, activation of distinct types of cells may play an important role in some diseases (e.g. [ 25 ]), in which case results of reference-free approaches could in principle depend upon the assumed level of complexity. Thus, critical to the algorithm is its sensitivity of results to choice of a parameter that represents the complexity, the dimension k of the latent linear association driven by cell composition, widely (though perhaps incorrectly) interpreted as the number of cell types.…”
Section: Introductionmentioning
confidence: 99%